Endoscopic Revision (StomaphyX) versus Formal Surgical Revision (Gastric Bypass) for Failed Vertical Band Gastroplasty - Johan Bolton; Richdeep S. Gill; Akram Al-Jahdali; Simon Byrns; Xinzhe Shi; Daniel W. Birch; Shahzeer Karmali (Journal of Obesity)
Background. Weight regain secondary to VBG pouch dilation is a typical referral for Bariatric surgeons. In this study we compare an endoluminal pouch reduction (Stomaphyx) to RYGB for revision. Methods. A retrospective review was completed for patients with a previous VBG presenting with weight regain between 2003–2010. Results. Thirty patients were identified for study 23 RYGB, 14 StomaphyX. Significant post procedure BMI loss was seen in each cohort (RYGB, 47.7 ± 7 kg/m2 to 35 ± 7 kg/m2; StomaphyX 43 ± 10 kg/m2 to 40 ± 9 kg/m2, P=0.0007). Whereas nausea and headache were the only complications observed in StomaphyX patients, the RYGB group had a 43.5% complication rate and 1 mortality. Complications following RYGB include: incisional hernia (13%), anastomotic leak (8.7%), respiratory failure (8.7%), fistula (8.7%), and perforation (4.35%). The median length of stay following RYGB was 6 days compared to 1.5 ± 0.5 days following StomaphyX. Conclusion. This study suggests that while RYGB revision may achieve greater weight loss, the complication rates and severity is discouraging. StomaphyX may be a safe alternative. Further technical modifications of the device and longer follow-up may clarify the role of this approach.